Prevention and Deterrence of Foreigners who Violate Immigration Regulations - I Gusti Putu Anom Kresna Wardana (Journal of Law and Border Protection, 2019)
Indonesia in dealing with the traffic of people into and out of its territory applies the Immigration Selective Policy Theory. This theory has the principle that only foreigners can provide benefits for the welfare of the people, nation and state, do not endanger security and order, and are not hostile towards the people who can enter and leave the territory of Indonesia. The formulation of the problem examined in this paper is how to prevent and deter foreigners who violate immigration regulations and how the concept of prevention and deterrence is in immigration control. The research method used is qualitative normative legal research and mixed logic (deductive and inductive). From the results of the research it can be seen that the efforts made by Indonesia in the prevention and deterrence of foreigners who violate the Immigration regulations by applying the provisions of article 75 point 2 of Law no. 6 of 2011 can be in the form of inclusion in the list of Prevention or deterrence, restrictions, changes, or cancellation of Stay Permits, prohibition of being in one or several certain places in the Indonesian Territory, the obligation to reside in a certain place in the Indonesian Territory, the imposition of fees , and / or deportation from the territory of Indonesia.